The Effect of Green Marketing on Purchase Decision on the Body Shop Indonesia Products (Case Study on the Body Shop Paris Van Java Bandung) - Cantika Martianti; Yuhana Astuti; Heppy Millanyani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The emergence of green marketing is an opportunity to improve the way consumers and producers make sustainable decisions for the environment, especially for the millennial generation. Seeing this phenomenon, one of the ones that runs green marketing in a sustainable manner is The Body Shop which emphasizes the essence of green marketing in their company. There are four dimensions to the green marketing variable, namely green product, green price, green place, green promotion. For purchasing decision variables, there are 6 dimensions, namely product selection, brand selection, dealer selection, purchase time, purchase amount, and payment method. Green marketing has a positive and significant effect on purchasing decisions for The Body Shop Paris Van Java Bandung products by millennials in the city of Bandung. The dimensions of green marketing (green product, green price, green place, green promotion) also have a positive and significant influence on purchasing decisions for The Body Shop Paris Van Java Bandung products by millennials in the city of Bandung. For the company The Body Shop Paris Van Java Bandung with its products it is expected to strengthen the green price factor.